2019
DOI: 10.3390/pr7100720
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Monitoring of Occupant’s Thermal State for Adaptive HVAC Predictive Controlling

Abstract: Conventional indoor climate design and control approaches are based on static thermal comfort/sensation models that view the building occupants as passive recipients of their thermal environment. Recent advances in wearable sensing technologies and their generated streaming data are providing a unique opportunity to understand the user's behaviour and to predict future needs. Estimation of thermal comfort is a challenging task given the subjectivity of human perception; this subjectivity is reflected in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…This study also showed that thermal efficiency in the heat recovery process proves that higher thermal conductivity produces higher heat transfer to the surface. Less amount of heat loss occurred during the study [11], [21]- [23].…”
Section: Introductionmentioning
confidence: 84%
“…This study also showed that thermal efficiency in the heat recovery process proves that higher thermal conductivity produces higher heat transfer to the surface. Less amount of heat loss occurred during the study [11], [21]- [23].…”
Section: Introductionmentioning
confidence: 84%
“…Model-Based Predictive Control Strategies: MBPC model-driven (or model-dependent) control strategies are mostly focusing on constructing an elaborate performance model in order to efficiently assess and choose the appropriate decisions that are estimated to present the greatest energy-efficiency potential [14][15][16][17][18][19][20].…”
Section: Related Work and Novelty Of The Papermentioning
confidence: 99%
“…To minimize overall system energy input or operating cost while still maintaining the satisfying indoor thermal comfort and healthy environment all kinds of control algorithms are employed on HVAC. In [3], model-based monitoring of the occupants' thermal state by predictive controlling was proposed. In [4], the supervisory and optimal controls were summarized and classified into the model-based methods which used physical models, gray-box models, and black-box models, and the model-free category which used expert systems and pure learning approaches.…”
Section: Background and Motivationmentioning
confidence: 99%